1999
DOI: 10.1209/epl/i1999-00159-8
|View full text |Cite
|
Sign up to set email alerts
|

Landau levels in the presence of a screw dislocation

Abstract: We study electrons moving in a magnetic field in the presence of a screw dislocation. We focus on the influence of the screw dislocation on the energy spectrum of the electron (or hole) in the magnetic field, in a continuum theory of defects that is isomorphic to three-dimensional gravity. We find exact expressions for the eigenfunctions and eigenvalues of the energy and verify that the infinite degeneracy of the Landau levels is broken by the unusual boundary conditions imposed by the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 15 publications
6
119
0
Order By: Relevance
“…Notice that this result is similar to the result obtained for Landau levels in the presence of a screw dislocation in [34]. Again, the infinite degeneracy of the Landau levels obtained in [16] is eliminated due the coupling of the torsion with the angular moment l, which agrees with the results given in [35].…”
Section: Landau Levels For a Neutral Particle In The Presence Ofsupporting
confidence: 89%
See 2 more Smart Citations
“…Notice that this result is similar to the result obtained for Landau levels in the presence of a screw dislocation in [34]. Again, the infinite degeneracy of the Landau levels obtained in [16] is eliminated due the coupling of the torsion with the angular moment l, which agrees with the results given in [35].…”
Section: Landau Levels For a Neutral Particle In The Presence Ofsupporting
confidence: 89%
“…In the same way as in the previous section, we find that the infinite degeneracy of the Landau levels obtained in [16] is broken since the parameters of the topology η and of the torsion χ in the expression (34) are not integer.…”
Section: Landau Levels For the Neutral Particle In The Presence Osupporting
confidence: 64%
See 1 more Smart Citation
“…In recent works, Landau quantization was studied in the presence of topological defects [35][36][37][38][39]. In [35,36] the influence of a disclination and dislocation in the energy levels was studied when an electron interacts with a magnetic field, respectively.…”
mentioning
confidence: 99%
“…In recent works, Landau quantization was studied in the presence of topological defects [35][36][37][38][39]. In [35,36] the influence of a disclination and dislocation in the energy levels was studied when an electron interacts with a magnetic field, respectively. In [37], the Landau levels of an electron interacting with an external magnetic field are obtained with a continuum distribution of topological defects, and it is shown that the presence of topological defects breaks the infinite degeneracy of the Landau levels.…”
mentioning
confidence: 99%